2016
DOI: 10.1002/mds.26463
|View full text |Cite
|
Sign up to set email alerts
|

Lewy body pathology involves the olfactory cells in Parkinson's disease and related disorders

Abstract: We detected Lewy body pathology in the olfactory epithelium in six of the eight patients with Parkinson's disease and in one patient with incidental Lewy body pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 14 publications
1
60
0
Order By: Relevance
“…These authors hypothesize that the odour threshold could be preserved in PD patients because of a relatively intact neuroepithelium in PD [26]. However, a recent neuropathological study found Lewy body pathology in the olfactory cells in the olfactory epithelium of PD patients [27]. This finding supports a damage of the olfactory epithelium and, thus, a possible impairment in smell detection or threshold in PD, which is in line with our results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These authors hypothesize that the odour threshold could be preserved in PD patients because of a relatively intact neuroepithelium in PD [26]. However, a recent neuropathological study found Lewy body pathology in the olfactory cells in the olfactory epithelium of PD patients [27]. This finding supports a damage of the olfactory epithelium and, thus, a possible impairment in smell detection or threshold in PD, which is in line with our results.…”
Section: Discussionsupporting
confidence: 83%
“…These deposits have a specific distribution in the central nervous system (CNS) [8] following Braak's stage hypothesis, where the first stage affects the olfactory bulb and the dorsal motor vagus nucleus. The olfactory deficit in PD seems to be explained, at least in part, by the abnormal α-synuclein deposition in olfactory structures within the CNS [9].…”
Section: Introductionmentioning
confidence: 99%
“…© 2016 KEY WORDS: IN VITRO PD MODEL; SUB-LETHAL CONCENTRATION OF 6-OHDA; APOPTOSIS; MITOCHONDRIAL MEMBRANE POTENTIAL; PHOSPHO SERINE129 a-SYNUCLEIN; VESICULAR MONOAMINE TRANSPORTER P arkinson 0 s disease (PD) is a chronic neurodegenerative disease characterized by selective loss of dopaminergic neurons in the substantia nigra (SN), distinct decrease in striatal dopamine level, and occurrence of cytoplasmic eosinophilic inclusions termed Lewy bodies (LBs); in the late stage of the disease. Though there are reports of other neuronal cell loss in the locus coeruleus and olfactory lobe during the disease development [Gesi et al, 2000;Fornai et al, 2005;Haehner et al, 2009;Saito et al, 2016], it has been identified that the with ubiquitin associates quite constantly with LBs, and also features in the dopaminergic neurons of sporadic PD cases. Biochemical and immunohistochemical studies in post mortem tissue of both familial and sporadic PD patient striata have showed that close to 90% of asynuclein deposited in LBs is phosphorylated at serine-129, as opposed to only 4% in the normal human brain [Fujiwara et al, 2002;Anderson et al, 2006].…”
mentioning
confidence: 96%
“…Biochem. 9999: 1-18, 2016. © 2016 KEY WORDS: IN VITRO PD MODEL; SUB-LETHAL CONCENTRATION OF 6-OHDA; APOPTOSIS; MITOCHONDRIAL MEMBRANE POTENTIAL; PHOSPHO SERINE129 a-SYNUCLEIN; VESICULAR MONOAMINE TRANSPORTER P arkinson 0 s disease (PD) is a chronic neurodegenerative disease characterized by selective loss of dopaminergic neurons in the substantia nigra (SN), distinct decrease in striatal dopamine level, and occurrence of cytoplasmic eosinophilic inclusions termed Lewy bodies (LBs); in the late stage of the disease.…”
mentioning
confidence: 99%
“…Clinical symptoms of PD involve motor dysfunction as muscle rigidity, bradykinesia, balance disturbances, resting tremor, and non-motor symptoms such as cognitive decline, depression and deficit in olfactory and gustatory systems in the early stages of the disease, and mood alterations, sleep disturbances and dementia especially in the late stages of the disease (Paillusson et al, 2016;Saito et al, 2016;Chao et al, 2015;Cecchini et al, 2014;Weintraub et al, 2008).…”
Section: Parkinson's Disease Developmentmentioning
confidence: 99%